Fixed point approach for weakly asymptotic stability of fractional differential inclusions involving impulsive effects - Ke, Tran Dinh; Lan, Do (Fixed point theory and algorithms for sciences and engineering, 2017)
We prove the global solvability and weakly asymptotic stability for a semilinear fractional differential inclusion subject to impulsive effects by analyzing behavior of its solutions on the half-line. Our analysis is based on a fixed point principle for condensing multi-valued maps, which is employed for solution operator acting on the space of piecewise continuous functions. The obtained results will be applied to a lattice fractional differential system.